2021
DOI: 10.4103/jiaomr.jiaomr_126_20
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Cryogun Versus Diode Laser Therapy in the Management of Oral Leukoplakia

Abstract: Background and Aim: This study was aimed to clinically evaluate the effectiveness of 810 nm diode laser and cryosurgery in the management of oral leukoplakia (OL) in terms of healing outcomes. Materials and Methods: Thirty subjects clinically and histo-pathologically diagnosed as having OL were randomly allocated into two groups. Group-1 consisting of 15 subjects each treated with cryotherapy, Group-2 was treated with an 810 nm diode Laser. VAS scale wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results of our study were in accordance with the studies performed by Kharadi et al .,[ 20 ] Reddy Kundoor et al .,[ 21 ] Praveen et al .,[ 22 , 23 ] Ramwala[ 24 ] and Chaudhri et al . [ 25 ] These studies concluded that the diode laser provides clinical improvement with minimal side effects and thus can be considered one of the best treatment modalities for leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were in accordance with the studies performed by Kharadi et al .,[ 20 ] Reddy Kundoor et al .,[ 21 ] Praveen et al .,[ 22 , 23 ] Ramwala[ 24 ] and Chaudhri et al . [ 25 ] These studies concluded that the diode laser provides clinical improvement with minimal side effects and thus can be considered one of the best treatment modalities for leukoplakia.…”
Section: Discussionmentioning
confidence: 99%